An Analysis of Compliment Expression Found in the Movie Entitled Afterlife of the Party - Putri, Lintang (LPPM Universitas Jambi, 2023)
This research analyzed the speech act of compliment found in the movie script Afterlife of the Party. This research was a qualitative descriptive study with a content analysis approach. The subjects of this research was all characters in Afterlife of the Party movie. The object of this research was the expression of compliment. This research used document analysis in data collection technique. The researcher applied the approach of Miles, Huberman, & Saldana (2014) to examine the overall data with the following steps: data collection, data condensation, data presentation, and drawing conclusions. Based on the findings, the researcher found (1) there are 5 types of linguistic form in the Afterlife of the Party movie namely type 1: noun/pronoun/noun phrase + is/look + (really) + adjective, type 2: I + (really) + like/love + noun phrase, type 3: pronoun + is + (a/an) + (really) + adjective + noun phrase, type 5: you + verb + noun phrase + (really) + adverb, type 7: what + (a/an) + adjective + noun phrase!, (2) there are 4 topics of compliment namely appearance, possession, personality, and ability, (3) there are 5 functions of compliment such as to express admiration, to maintain solidarity, to replacing other speech act formulas, to soften threat, to be a conversation strategy.